Synthesis of practice planning for small and medium-sized communities. - National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, National Research Council, 1984)
Presents 26 case studies taken from the National Conference on Transportation Planning for Small and Medium-Sized Communities held Dec. 1978 in Sarasota, Fla.
Cover title.
August 1984.
Includes bibliographical references.
Keywords: Transportation -- Planning; Urban transportation -- Planning